Taste, smell and food-related nausea and vomiting responses in hyperemesis gravidarum: A case-controlled study - Tan, Peng Chiong; Kartik, Balaraman; Thanendran, Panjaratnam; Zakaria, Rozita; Win, Sandar Tin; Omar, Siti Zawiah (Nature Research, 2020)
A case-controlled study was performed to evaluate taste and smell impairment, nausea or vomiting (NV) response to taste and smell and toleration to food texture, item and cooking method in hyperemesis gravidarum patients (HG) compared to gestation-matched controls from a university hospital and primary care clinic in Malaysia. Taste strips (4 base tastes), sniff sticks (16 selected smells) and a food-related questionnaire were used. 124 participants were recruited. Taste impairment was found in 13%(8/62) vs. 0%(0/62) P = 0.003 and the median for correct smell identification was 5[4–6] vs. 9[7–9] P < 0.001 in HG vs. controls. In HG, bitter was most likely (32%) and sweet taste least likely (5%) to provoke NV. In both arms, fish smell was most likely to provoke NV, 77% vs. 32% P < 0.001 and peppermint smell least likely 10% vs. 0% P = 0.012; NV response was significantly more likely for HG arm in 10/16 smells. In HG, worst and best NV responses to food-texture were pasty 69% and crunchy 26%; food-item, plain rice 71% and apple 16% and cooking-style, deep-frying 71% and steaming 55%. HG demonstrated taste and smell impairment and increased NV responses to many tastes and smells. Crunchy sweet uncooked food (apple or watermelon) maybe best tolerated in HG. © 2020, The Author(s).